Dialogic listening: how music may help us become better philosophers (2019)
This paper is about dialogic listening as a precondition for meaningful engagement in Socratic dialogues and for music. In order to arrive at a better understanding of what constitutes dialogic listening in the context of educational philosophical dialogues, I first shed light on the practice of philosophy teaching based on Nelson & Heckmann’s neo-Socratic paradigm and link this practice to Plato’s dialogues. I then argue that the activity of listening to an interlocutor during Socratic dialogues on the one hand, and listening to music on the other, may in both cases be understood as a precondition for the process of engagement and, consequently, the co-creation of meaning as a central objective to the philosophical practice. I show this by discussing both Buber and Gadamer, combining their insights into three interrelated features of dialogic listening: 1) openness, 2) reciprocity, and 3) awareness, which apply to both philosophical dialogues and music. Ultimately, I attempt to make a case for the complementary application of music in the philosophical educational practice.